microRNA-145 Mediates the Inhibitory Effect of Adipose Tissue-Derived Stromal Cells on Prostate Cancer - Takahara, Kiyoshi; Ii, Masaaki; Inamoto, Teruo; Nakagawa, Takatoshi; Ibuki, Naokazu; Yoshikawa, Yuki; Tsujino, Takuya; Uchimoto, Taizo; Saito, Kenkichi; Takai, Tomoaki; Tanda, Naoki; Minami, Koichiro; et al. (Stem cells and development, 2016)
Adipose-derived stromal cell (ASC), known as one of the mesenchymal stem cells (MSCs), is a promising tool for regenerative medicine; however, the effect of ASCs on tumor growth has not been studied sufficiently. We investigated the hypothesis that ASCs have an inhibitory effect on metastatic tumor progression. To evaluate the in vitro inhibitory effect of ASCs on metastatic prostate cancer (PCa), direct coculture and indirect separate culture experiments with PC3M-luc2 cells and human ASCs were performed, and ASCs were administered to PC3M-luc2 cell-derived tumor-bearing nude mice for in vivo experiment. We also performed exosome microRNA (miRNA) array analysis to explore a mechanistic insight into the effect of ASCs on PCa cell proliferation/apoptosis. Both in vitro and in vivo experiments exhibited the inhibitory effect of ASCs on PC3M-luc2 cell proliferation, inducing apoptosis and PCa growth, respectively. Among upregulated miRNAs in ASCs compared with fibroblasts, we focused on miR-145, which was known as a tumor suppressor. ASC-derived conditioned medium (CM) significantly inhibited PC3M-luc2 cell proliferation, inducing apoptosis, but the effect was canceled by miR-145 knockdown in ASCs. ASC miR-145 knockdown CM also reduced the expression of Caspase 3/7 with increased antiapoptotic protein, BclxL, expression in PC3M-luc2 cells. This study provides preclinical data that ASCs inhibit PCa growth, inducing PCa cell apoptosis with reduced activity of BclxL, at least in part, by miR-145, including exosomes released from ASCs, suggesting that ASC administration could be a novel and promising therapeutic strategy in patients with PCa.